Variability in Arrival Time of White Storks (Ciconia ciconia L.): Impact of Age, Interindividual Variation, and Global Change - Athamnia, Mohammed; Belabed, Bourhane-Eddine; Samraoui, Kenz Raouf; Boucheker, Abdennour; Touati, Laïd; Samraoui, Farrah; El-Serehy, Hamed A.; Samraoui, Boudjéma (Frontiers in Ecology and Evolution, 2022)
1. Global changes are inducing migratory birds to advance their annual cycle. However, changes in the time of arrival at their breeding grounds have significant fitness implications. 2. This study aims to identify factors affecting the variability in arrival time of migratory white storks (Ciconia ciconia L.) and to determine if their arrival at North African breeding grounds is occurring earlier. 3. We monitored the arrival of ringed white storks at a breeding colony in Algeria between 2017 and 2021. The birds arrived at this breeding colony over an extended period spanning mid-December to mid-June each year. 4. We found that stork arrival was negatively correlated with age and year of arrival, with older birds arriving first and stragglers consisting of first- and second-year birds arriving later. Notably, arrivals have been shifting towards earlier dates at this breeding ground. Furthermore, cluster analysis of arrival dates for each age-class revealed two distinct groups comprising early and late arrivals. 5. Advancement of the annual cycle of the North African white stork population is consistent with phenological shifts induced by global changes and that have been recorded globally in a wide range of living organisms.